(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of this article is to analyze telework, presenting its general definition and its characteristics and proportions achieved with the covid 19 pandemic in Brazil. To achieve this goal, an approach will be made to the dynamics of teleworking, and the positive and negative consequences that this modality can present, bringing telemedicine to the fore. The deductive approach method and the indirect documentation search technique were used, using doctrinal, jurisprudential and documentary research.